2019
DOI: 10.3892/br.2019.1257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microRNA‑9 and ‑192 expression levels as biomarkers in patients suffering from breast cancer

Abstract: Given the global outbreak of breast cancer and its debilitating effect on women's health, it is not surprising that tremendous efforts have been made with an aim of shedding more light on the mechanisms involved in the pathogenesis of this type of cancer. Among the long list of risk factors associated with this malignancy, recently, the role of microRNAs (miRNAs or miRs) has turned into a hotspot for breast cancer investigations. miRNAs approximately 20 nucleotides in length and are located in either an exon o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Protein phosphatase-1 negatively regulates Aurora A -63]. The expression of microRNAs has been reported in cancers [64][65][66][67][68][69]. Specifically, microRNAs such are miR-346 and miR-361-3p were suggested to modulate the expression of PSA, TMPRSS2 and DRG1 in prostate cancer [70].…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase-1 negatively regulates Aurora A -63]. The expression of microRNAs has been reported in cancers [64][65][66][67][68][69]. Specifically, microRNAs such are miR-346 and miR-361-3p were suggested to modulate the expression of PSA, TMPRSS2 and DRG1 in prostate cancer [70].…”
Section: Discussionmentioning
confidence: 99%
“…Others described an unclear role of miR-9-5p in tumor tissues and BC cells, suggesting that its function may depend on different subtypes of BC or progression level (Krell et al, 2012;Hasanzadeh et al, 2016;Shi et al, 2017). Curiously, a group reported different expression levels of miR-9-5p in tissues compared to serum of BC patients (Tavakolian et al, 2019). Previous findings revealed that miR-9-5p expression can be influenced by steroid hormone receptors, and that it is implicated in a regulatory mechanism signaling in BC, besides being involved in affecting the biology of the tumor microenvironment (Zhuang et al, 2012;Pillai et al, 2014;Baroni et al, 2016;Barbano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, extensive evidence points to largely altered expression levels of miRNAs in various types of cancers; and suggests the immense diagnostic potential of miRNA alteration, specifically circulating miRNAs, as biomarkers [21]. The diagnostic value of many circulating miRNAs has been reported for both chronic and acute leukemia (e.g., miR-10, miR-29, miR-31, miR-34, miR-130b, miR-146a, miR-148, miR-150, miR-155, miR-181b-5p, miR-192, miR-203, miR-210, miR-212, miR-328, miR-335, miR-342, miR-375) [22][23][24][25][26][27], breast cancer (e.g., miR-9, miR-10b, miR-21, miR-155, miR-181a-5p and miR-192) [28][29][30][31][32], lung cancer (e.g., miR-7, miR-25, miR-193a-3p, miR-214, and miR-483-5p) [33][34][35][36][37], and other human cancers [38], to name just a few. Besides cancer, circulating miRNAs are also implicated in the diagnosis of cardiovascular diseases and neurodegenerative diseases.…”
Section: Mirna As Clinical Biomarkersmentioning
confidence: 99%